PERSEPSI SISWA TATA BOGA TENTANG PENERAPAN SANITASI DAN HIGIENE DI KANTIN SEKOLAH MENENGAH KEJURUAN - Siti Hartini Marasabessy (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2019)
The purpose of the study was to find out perceptions of students about the application of sanitation and hygiene in the canteen. The type of this research is quantitative descriptive. The technique of collecting data used a questionnaire. The instrument of this research was a questionnaire. Data analysis techniques used descriptive analysis to look for mean values, standard deviations, medians, and modes. The results showed that students' perceptions of sanitation in the canteen with a relative frequency of 64.42% in the high category and students' perceptions of hygiene in canteens with a frequency of 53.69% in sufficient categories, meaning that students' perceptions of the application of sanitation in canteens are higher than students' perceptions of applying hygiene in the canteen.